Comparative Life-Cycle assessment of microalgal biomass production in conventional growth media versus newly developed nanoemulsion media. (May 2022) - Nigam, Harshita; Jain, Rahul; Malik, Anushree; Singh, Vikram
Graphical abstract: Highlights: Both midpoint and endpoint analysis were performed using ReCiPe 2016 method. Two times less CO2  eq. release with nanoemeulsion compared to conventional media. Bioreactor material and electricity usage were major contributors in algal cultivation. Process challenges were identified and improvement measures suggested. Abstract: Microalgae biomass is a potential feedstock for biodiesel, animal feed, biofertilizer, and other products such as bioactive compounds. Most of the reported studies describe microalgae as a green process, however, the impacts associated with its growth media and cultivation have seldom been studied. With an aim to analyze the environmental impacts, the present study compares the life-cycle assessment of microalgal cultivation in two growth media. The data used was obtained from the experimental sets where microalgae  C. pyrenoidosa  was cultivated in BG11 (control or SC-1) and silicone oil nanoemulsion (previously developed medium or SC-2) on a lab scale. The environmental impacts were evaluated using the ReCiPe midpoint and endpoint method using Sima Pro 9.0 software based on a "cradle-to-gate" approach. The total environmental score for 1 kg microalgal biomass production was 99.25Pt in SC-1, and 53.39Pt in SC-2, concluding greater environmental burden by SC-1. The photobioreactor construction material along with the operation led to maximum emissions, human toxicity, and resource depletion. In summary, the newly developed nanoemulsion medium was found to be eco-friendly that has the potential to minimize the usage of conventional nutrients and resources.